2015
DOI: 10.1111/jtxs.12124
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effects of Different Fermentation Methods on Dough Characteristics

Abstract: Dough characteristics as affected by different preferment types and fermentation times were evaluated. A dough type was obtained with yeasted stiff preferment (60% water), fermented for a long period (biga-type dough -B) and another one made with a semiliquid preferment (100% water), obtained with sourdough and fermented for a short period (poolish-type dough -P). The doughs obtained were compared with a standard dough (direct dough -D). During the first 60 min of fermentation, pH, titratable acidity, volume, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 27 publications
(56 reference statements)
2
15
0
Order By: Relevance
“…Significant correlations were recorded between increasing fermentation time and decreasing number of gas cells in class 1 in group of Ss formula 0.40 (0.98) Ts_0.30 (0.92) and Ts_0.15 (0.97), and increasing the number of gas cells in the same group in class 2, namely (0.78; 0.98; and 0.73), on the other hand. These results correspond to Balestra et al () who confirmed the majority of gas cells are in first classes (0–0.01).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Significant correlations were recorded between increasing fermentation time and decreasing number of gas cells in class 1 in group of Ss formula 0.40 (0.98) Ts_0.30 (0.92) and Ts_0.15 (0.97), and increasing the number of gas cells in the same group in class 2, namely (0.78; 0.98; and 0.73), on the other hand. These results correspond to Balestra et al () who confirmed the majority of gas cells are in first classes (0–0.01).…”
Section: Resultssupporting
confidence: 92%
“…This indicated that the structure of all dough was compact, with open structure. Those results showed uniform fermentation in dough (Balestra, Pinnavaia, & Romani, ). Decreased salt concentrations most significantly affected class 1 and class 2.…”
Section: Resultsmentioning
confidence: 84%
“…Therefore, pH and TTA values in Table 2 and Figure 1 could be inconsistent because LAB fermentation is a live biological system and consistency could not always be reach in this kind of systems. Moreover, the changes in the acidity levels of the tested doughs could be influenced by yeast-produced carbon dioxide ( Balestra et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The fermented batter was heated in a MW oven (NE‐1753, Panasonic, Kadoma, Osaka, Japan) for 2 min at 4.25 W/g and cooled for 1 hr to room temperature for analysis. The design also included a blank without sourdough addition and a control with the addition of chemically acidified dough (a mixture of lactic acid and acetic acid was used to obtain dough with a pH value to that of the sourdough) (Balestra, Pinnavaia, & Romani, 2015). In addition, SSC was steamed in a cottage steamer (HLHB24‐2, SIEMENS, Berlin, Germany) for 15 min.…”
Section: Methodsmentioning
confidence: 99%